Atypical HSV-2 Meningoencephalitis in an Immunocompetent Patient: A Case Report - Ghiletchi, Angela; Coelho, Carolina; Ferreira, Inês; Fiúza M. Rua, Inês; Cabaço, Sérgio; Moniz, Wendy; Nazário Leão, Rodrigo (International Journal of Innovative Research in Medical Science, 2024)
Herpes simplex virus type 2 (HSV-2) is primarily known for causing genital infections but can occasionally result in central nervous system (CNS) involvement, manifesting as meningitis or meningoencephalitis. HSV-2 meningoencephalitis is a rare, yet potentially severe condition, particularly in immunocompromised patients. We present the case of a 63-year-old immunocompetent woman who developed progressive neurological symptoms, including mental confusion and generalized seizures. Cerebrospinal fluid analysis and polymerase chain reaction (PCR) confirmed HSV-2 infection. Timely initiation of acyclovir led to a favourable outcome, with the patient being discharged after 15 days of antiviral therapy without any lasting neurological sequelae. This case highlights the importance of early recognition and treatment of HSV-2 meningoencephalitis, even in immunocompetent patients, to prevent long-term complications.